Green Technology Kit: A Development Learning Media with AI for SDGs - Achmad Ali Fikri; Salmanera Senja Lopiani; Iin Uswatun Hasanah (International Journal of Learning Media on Natural Science (IJLENS), 2024)
Learning is currently experiencing a shift from conventional learning in the classroom to internet-based virtual learning via mobile devices, artificial intelligence and outdoor class. Furthermore, cases of environmental pollution due to used cooking oil in Indonesia are quite high, reaching 3.8 million tons every year. In these cases, needed a technology that can be a solution for recycling use cooking oil waste into product with positif value which is biodiesel. The aim of this research is to develop learning media and technology that can process used cooking oil waste into products with positive value, one of which is biodiesel. This type of research is research and development with a Borg & Gall model which involves ten steps. The subjects of this research were residents of Getaspejaten Village, Kudus Regency with a sample of twenty residents. The data in this research includes assessment data from validators and field trial. Data collected using a product feasibility assessment questionnaire with the help of Google forms. Data analysis was carried out using the Rasch Model assisted by the Ministep application. This research resulted in a technology called GT KIT: Green Technology KIT which is feasible to use as a learning media, seen from the analysis of field test data which shows the raw variance explained with a measurement value of 36% so that it can be said that the GT KIT was developed to meet the eligibility criteria. The development of the GT KIT product was accompanied by the development of AI technology in the form of a fast-messaging service called 'GT KIT BOT' to make it easier for anyone to get solutions or responses to problems that might come up. With the GT KIT as a technology that makes it easier for studentsunderstanding the concept of environmental pollution and to process used cooking oil waste themselves, it is hoped that environmental pollution can be reduced and an alternative substitute for diesel fuel in the form of biodiesel can be created.